Investigating the impact of automated instruments used for assessing the writing skill: Perspectives of language e-learners - Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2024)
The main goal of using Automated Writing Evaluation (AWE) instruments is to help language learners learn more quickly and more effectively. In addition to assigning writing-related assignments, these technologies give language learners a suitable forum where they can receive general comments on their written pieces. In the same vein as the benefits of using AWE instruments, this study aims to comprehend foreign language e-learners' perspectives regarding the impact of these tools in their learning environment. Sixty-seven (67) research participants, who are currently e-learning foreign languages at King Khalid University, participated in an online survey to achieve this fundamental goal. Their answers to the questions were compiled and presented using a quantitative method, and they serve as the foundation for the research results. Moreover, the data distribution was precisely computed using a descriptive statistics table. Nonetheless, the study's findings demonstrate that AWE tools come with suitable measurements that non-native English speakers might utilize to improve their writing skills. This is predicated on the scoring propensity and feedback propensity—two crucial aspects of these instruments. Additionally, the study shows that e-learners occasionally run into difficulties when using these resources, which are mostly remediable by the programmers of these applications as well as language teachers. Lastly, to achieve a balance in the appropriate integration and use of AWE tools in the language educational setting, this research recommends using these tools in addition to human feedback and instruction.